The Use of Weblog in Improving Students’ Writing Skill - Muhammad Fahreza; Zulfadli A. Aziz; Nurul Inayah (Research in English and Education Journal, 2017)
This research is aimed at finding out whether the use of weblog improves students’ writing skill at SMPN 9 Banda Aceh or not. The sample of this research was the second grade students in the class of VII-1. The researcher used pre-experimental research with one group pre-test post-test design in analyzing the significant improvement. The data were gained quantitatively by administering pre-test and post-test. In analyzing the data, the researcher used statistical formula mean score and t-test. The finding shows that the mean score in the post-test was higher than in pretest. It shows that the mean score of posttest is higher (75) than the pretest score (57), so the different scores of the tests is 18. Moreover, the analysis of t-test showed that tscore ttable or 8.714 2.074 at the level of significance 0.05 with the degree of freedom (df) 22. The higher aspects were content and vocabulary (16 Point). Based on these results, it can be concluded that Ha is accepted and Ho is rejected. It suggests that the use of weblog can improve students’ writing skills in all aspects. Therefore, the Weblog is recommended as a good media in teaching writing.